Iodide‐Mediated Rapid and Sensitive Surface Etching of Gold Nanostars for Biosensing. Issue 18 (24th March 2021) - Xianyu, Yunlei; Lin, Yiyang; Chen, Qu; Belessiotis‐Richards, Alexis; Stevens, Molly M.; Thomas, Michael R.
Abstract: Iodide‐mediated surface etching can tailor the surface plasmon resonance of gold nanostars through etching of the high‐energy facets of the nanoparticle protrusions in a rapid and sensitive way. By exploring the underlying mechanisms of this etching and the key parameters influencing it (such as iodide, oxygen, pH, and temperature), we show its potential in a sensitive biosensing system. Horseradish peroxidase‐catalyzed oxidation of iodide enables control of the etching of gold nanostars to spherical gold nanoparticles, where the resulting spectral shift in the surface plasmon resonance yields a distinct color change of the solution. We further develop this enzyme‐modulated surface etching of gold nanostars into a versatile platform for plasmonic immunoassays, where a high sensitivity is possible by signal amplification via magnetic beads and click chemistry. Abstract : We outline a rapid and sensitive nanoparticle etching‐based strategy for biosensing. Iodide modulates the plasmonic features of gold nanostars by etching them into spherical nanoparticles, being a versatile biosensing platform for enzyme detection and plasmonic immunoassays.